Live feeds in marine aquaculture - Stottrup, Josianne G. (Blackwell Science, 2003)
Text provides information on feeding of cultivated fish and shellfish. Covers in detail the biology and culture of the main live prey and microalgae used as feeds in the aquaculture of major commercial species including shrimps, sea bass, halibut, cod and bivalves. For fish farmers, researchers, and personnel in feed and equipment companies supplying the aquaculture trade.